2020
DOI: 10.1155/2020/6062478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Strategies on Glucose Homeostasis in Gestational Diabetes Mellitus: A Systematic Review and Network Meta-Analysis

Abstract: Background. Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy, and nutritional therapy is the basis of GDM treatment. However, the effects of different forms of nutritional supplementation on improving gestational diabetes are uncertain. Objective. We conducted a network meta-analysis to evaluate the effects of supplementation with different nutrients on glucose metabolism in women with GDM. Methods. We conducted a literature search using PubMed, EMBASE, and the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Mg supplementation has been reported to reduce the risk of GDM in hypomagnesemia pregnant women [59]. A recent meta-analysis indicated that Mg supplementation was far more effective than other nutrients supplementation in maintaining glucose metabolic homeostasis and decreasing serum insulin in women with GDM [60]. Mg is required in multiple steps of the insulin-signaling pathways, and the depletion of it can affect the process of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Mg supplementation has been reported to reduce the risk of GDM in hypomagnesemia pregnant women [59]. A recent meta-analysis indicated that Mg supplementation was far more effective than other nutrients supplementation in maintaining glucose metabolic homeostasis and decreasing serum insulin in women with GDM [60]. Mg is required in multiple steps of the insulin-signaling pathways, and the depletion of it can affect the process of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of heterogeneity was substantial, the point estimates for the majority of the included studies were in the same direction favoring probiotics. Our findings on FPG corroborated the previous meta-analyses [ 27 , 35 , 37 , 38 , 44 ] that reported the effects of probiotics on glycemic outcomes in GDM. By contrast, Han et al [ 43 ] reported no significant reduction in FPG after probiotics supplementation in women with GDM.…”
Section: Discussionsupporting
confidence: 91%
“…Previous meta-analyses explored the effects of probiotic intervention on glycemic control [35][36][37][38][39][40][41][42], and limited meta-analyses analyzed lipid metabolism [39,40,43,44], inflammatory [27,44], oxidative stress [27,44], and pregnancy outcomes in pregnant women with GDM [41,43,44]. The majority of these reviews suggested that probiotic supplementation has beneficial effects on glycemic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Мета-аналіз 2020 р. [24] показав, що добавки магнію корисніші для зниження сироваткового інсуліну в порівнянні з пробіотиками (-5,10 мМО/мл, 95% довірчий інтервал (ДІ) від -9,32 до -0,88) і плацебо (-7,80 мМО/мл, 95% ДІ від -9,32 до -0,88).…”
Section: аналіз літературних даних і постановка завдання дослідженняunclassified